Incisional negative pressure wound therapy to reduce surgical-site infections in major limb amputations: a meta-analysis. Issue 8 (4th August 2022) - Frodl, A; Geisteuer, N; Fuchs, A; Nymark, T; Schmal, H
Abstract : Purpose: Incisional negative pressure wound therapy (iNPWT) has shown effectiveness in the treatment of high-risk surgical wounds. Especially patients with diabetes-induced peripheral arterial disease undergoing major limb amputation have a high intrinsic risk for post-surgical wound infections. While normal gauze wound dressings do not cause stimulation of microvasculature, iNPWT might improve wound healing and reduce wound complications. The purpose of this study was to systematically review the literature for rates of wound complications and readmissions, as well as post-surgical 30- day mortality. Methods: We conducted a systematic review searching the Cochrane, PubMed, and Ovid databases. Inclusion criteria were the modified Coleman methodology Score >60, non-traumatic major limb amputation, and adult patients. Traumatic amputations and animal studies were excluded. Relevant articles were reviewed independently by referring to the title and abstract. In a meta-analysis, we compared 3 studies and 457 patients. Results: A significantly overall lower rate of postoperative complications is associated with usage of iNPWT (odds ratio (OR) = 0.52; 95% CI: 0.30–0.89; P = 0.02). There was no significant improvement for 30- day mortality, when iNPWT was used (OR= 081; 95% CI: 0.46 – 1.45; P = 0.48). Nevertheless, we did not note a significant difference in the readmission rate or revision surgery between the two groups. Conclusion: Overall, the usage of iNPWT may reduce the risk of postoperative wound complications in major lower limb amputations but does not improve 30- day mortality rates significantly. However, to anticipate surgical-site infection, iNPWT has shown effectiveness and thus should be used whenever applicable.